HADITH SUTRAH: STUDY OF MA'ANIL HADITH - Zulfikar (The Islamic Education and Multiculturalism Foundation, 2020)
Abstract: This study talks about the understanding of the hadith about the sutras. I think this theme is important to discuss. To obtain a comprehensive meaning and understanding of the substance of the meaning of a hadith, in this study the author does this by considering several aspects in understanding the hadith of the Prophet SAW. such as asbabul wurud, observing variants of hadith texts, collecting meaningful traditions and looking for meanings that are relevant to the current context. In the hadith about the sutras narrated by Abu Dharr r.a, there is an order from the Prophet SAW. to make a sutrah / barrier that aims to maintain solemnity in performing prayers. If someone who prays does not make a sutrah in front of him, then his prayer will be invalid if passed by donkeys, women and black dogs. However, in the hadith narrated by Aisyah r.a, she said that she was lying in front of the Prophet SAW who was praying. Hadith regarding this sutra has a very varied meaning. According to the opinion of the majority of scholars, the hadith narrated by Abu Dharr r.a and Aisyah r.a do not contradict each other, in the hadith of A'Isyah r.a it is said that Aisyah r.a just lay in front of the Prophet SAW. who are praying, not passing.